Characterization and sensitivity to pollutants of cholinesterases in the Antarctic scallop Adamussium colbecki - BONACCI, S.; CORSI, I.; FOCARDI, S. (Ecotoxicology and Environmental Safety, 2009)
Antarctica is affected by man-made contamination and development of sensitive ecotoxicological tools for impact assessment is a priority task. The aims of the present study were to characterize cholinesterase (ChE) activities in an Antarctic key species, the scallop Adamussium colbecki, and to investigate their sensitivity as biological markers (biomarkers) of exposure to pollutants and of their effects. Our results show that ChEs in gills share most characteristics with true acetylcholinesterase. The present results show that ChE activities in A. colbecki are significantly inhibited by organophosphates (OPs) and somehow affected by in vitro exposure to mixtures of marine contaminants such as polycyclic aromatic hydrocarbons (PAHs), even if no concentration-dependent pattern of response was observed and no effect was elicited by polychlorinated biphenyls (PCBs). The present results do not demonstrate ChEs in A. colbecki as sensitive tools to measure exposure to the above chemicals, but they may be worthy of further study considering the importance of the scallop in Antarctic marine ecosystems and its suitability as a sentinel species. © 2009 Elsevier Inc. All rights reserved.